A review on benchmarking of supply chain performance measures - Wong, Wai Peng; Wong, Kuan Yew (Emerald Group Publishing Ltd., 2008)
Purpose - To redress the imbalances in the past literature of supply chain benchmarking and enhance data envelopment analysis (DEA) modelling approach in supply chain benchmarking.